PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, KEBIJAKAN DIVIDEN DAN TINGKAT SUKU BUNGA TERHADAP NILAI PERUSAHAAN - Maimunah, Siti; Hilal, Suhaila (Universitas Pakuan, 2014)
ABSTRACTThe management company has a goal to enhance the value of the company through the implementation of financial decisions consisting of investment decisions, financing decisions, and dividend policy. Therefore, the implementation should be done carefully and precisely, given any financial decisions taken will affect other financial decisions and will have an impact on the achievement of company objectives. This study aims to determine whether the investment decisions (Capital expenditure to book value of assets), the decision of funding (debt to equity ratio) and dividend policy (dividend payout ratio) affects the value of the company (Price Book Value) either simultaneously or partially on the PT Mayora Indah, Tbk. period 2004-2013 using secondary data from the financial statements and the price of the shares of PT Mayora Indah Tbk. within the last ten years from 2004 to 2013. The analysis method of multiple linear regression analysis is presented using SPSS version 21. Results of the study revealed that (1) the outcome of the investment conveyed a partially negative effect on the value of the company, (2) the decision is funding a partially positive effect on firm value, (3) partial dividend policy does not affect the value of the company, and (4) simultaneously or jointly variable investment decisions, financing decisions, and dividend policy portrayed a positive effect on firm value. Additionally, variable investment decisions, financing, and dividend policy decisions affect the value of the company, amounting to 83.5% while the remaining 16.5% is influenced by other variables not included in the regression model.Keywords : fixed asset growth, Total Asset, Total debt, Total Equity, Dividend per Share, Earning per Share, Stock Price, Price Book Value